2020
DOI: 10.3389/fendo.2020.555931
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Bone Marrow Heterogeneity Using Texture Analysis of Chemical Shift Encoding-Based MRI: Variations in Age, Sex, and Anatomical Location

Abstract: Objective: Vertebral bone marrow composition has been extensively studied in the past and shown potential as imaging biomarker for osteoporosis, hematopoietic, and metabolic disorders. However, beyond quantitative assessment of bone marrow fat, little is known about its heterogeneity. Therefore, we investigated bone marrow heterogeneity of the lumbar spine using texture analysis of chemical-shift-encoding (CSE-MRI) based proton density fat fraction (PDFF) maps and its association with age, sex, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Water-fat separation was performed using a graph-cut algorithm, employing a multi-peak fat model specific to bone marrow and a single T2* decay model ( 49 , 50 ). The PDFF maps were computed as the ratio of the fat signal over the sum of fat and water signals ( 29 , 51 , 52 ). T2* maps were extracted in addition to PDFF maps.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water-fat separation was performed using a graph-cut algorithm, employing a multi-peak fat model specific to bone marrow and a single T2* decay model ( 49 , 50 ). The PDFF maps were computed as the ratio of the fat signal over the sum of fat and water signals ( 29 , 51 , 52 ). T2* maps were extracted in addition to PDFF maps.…”
Section: Methodsmentioning
confidence: 99%
“…The vertebral bodies were manually segmented using sagittal images. In the reconstructed maps, manual polygonal ROIs were carefully placed to enclose the vertebral body using MITK ([ ]; German Cancer Research Center, Division of Medical and Biological Informatics, Medical Imaging Interaction Toolkit, Heidelberg, Germany; Figures 1 and 3 ) ( 51 , 52 ). The segmentations did not include the posterior elements and were performed by the same radiologist who had also performed visual inspection of the results of the CNN-based algorithm for CT data processing (two years of experience in spine imaging, M.D.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CSE-MRI conducted in 156 subjects at 3T (8 echoes 3D spoiled gradient echo sequence, voxel size 0.98 mm × 0.98 mm × 4.00 mm, acq. time 1:17 min), showed that vertebral bone marrow heterogeneity is primarily dependent on sex and age but not on anatomical location suggesting that future studies should investigate the bone marrow heterogeneity with regards to aging and disease [ 141 ]. Baum et al in a study conducted on the whole spine of 28 young and healthy patients using CSE-MRI at 3T (8 echoes, acq.…”
Section: Prospectivesmentioning
confidence: 99%
“…Regarding musculoskeletal imaging, TA has predominantly been performed on non-quantitative data, such as sonography [ 26 ], computed tomography [ 27 ], or conventional T2-weighted MRI sequences [ 28 , 29 ]. Furthermore, TA based on CSE-MRI-derived PDFF maps has been used in the quantitative analysis of vertebral bone marrow [ 30 , 31 ]. In this regard, PDFF-based TA can be considered superior in its ability to reveal information on muscular fat distribution and consequently differentiate muscles with different patterns of fatty infiltration.…”
Section: Introductionmentioning
confidence: 99%